Ligularia phoenicochaeta (Franchet) Liu (1987) is a later isonym of L. phoenicochaeta (Franchet) Handel-Mazzetti (1925) - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2017)
Senecio phoenicochaetus Franchet (1892: 295; “phaenicochaetus”) was described on the basis of two collections, J.M. Delavay 2191 (P) and J.M. Delavay 2473 (A, K, P), from Lijiang, northwestern Yunnan, China. It was recognized as a distinct species either in Cremanthodium Bentham (1873: 37) (Good 1929, Handel-Mazzetti 1936, Hu 1966, Wu 1984, Min 2014) or in Ligularia Cassini (1816: 198) (Handel-Mazzetti 1925, Liu 1987, 1989, Chen & Li 1994, Liu & Illarionova 2011) by all the later authors but Kitamura (1939), who treated it as Senecillis phoenicochaeta (Franchet) Kitamura (1939: 87; “phaenicochaeta”). Senecillis Gaertner (1791: 453), however, was later sunk as a section of Ligularia, i.e. L. sect. Senecillis (Gaertner) Kitamura (1942: 187).